PENGARUH KURS, INFLASI, LIBOR DAN PDB TERHADAP FOREIGN DIRECT INVESMENT (FDI) DI INDONESIA - Rexsy S Tambunan; Yusbar Yusuf; Anthoni Mayes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the effect of the influence of Exchange Rates, Inflation, Libor, and GDP to the Foreign Direct Invesment (FDI) In Indonesia. The data used in this study is a time series data from 1998 to 2013 were sourced from Invesment Coordinating Board (Badan Koordinasi Penanaman Modal), Bank Indonesia, and Central Bureau of Statistics (Badan Pusat Statisitik). This study used quantitative research methods, and analyzed using multiple linear regression analysis using SPSS 20 application for Windows computers. In this study, the independent variable is Exchange Rates (X1), Inflation (X2), Libor (X3), and GDP (X4), while the dependent is realitation Foreign Direct Invesment (Y).This study tested the hypothesis of regression coefficient (coefficient of determination, a significant test concurrent / F test, and the significant individual test / t test). The result showed that the variable Exchange Rates, Inflation, libor and GDP at once / simultaneously have a significant influence on the realitation Foreign Direct Invesment (FDI). The individual test / partial showed that Gross Domestic Product variable acquired that contributes greater than the variable rate of Exchange Rates, Inflation,and Libor ont the realitation Foreign Direct Invesment (FDI).Keywords:Exchange Rate, Inflation, London Inter Bank Offering Rate (LIBOR), Gross Domestic Product (GDP), and Foreign Direct Invesment (FDI).